Greater sensitivity to multiple sclerosis disability worsening and progression events using a roving versus a fixed reference value in a prospective cohort study. (June 2018) - Kappos, Ludwig; Butzkueven, Helmut; Wiendl, Heinz; Spelman, Timothy; Pellegrini, Fabio; Chen, Yi; Dong, Qunming; Koendgen, Harold; Belachew, Shibeshih; Trojano, Maria
Background: Confirmed Expanded Disability Status Scale (EDSS) progression occurring after a fixed-study entry baseline is a common measure of disability increase in relapsing-remitting multiple sclerosis (RRMS) studies but may not detect all disability progression events, especially those unrelated to overt relapses. Objective: To evaluate possible measures of disability progression unrelated to relapse using EDSS data over ≈5.5 years from the Tysabri ® Observational Program (TOP). Methods: TOP is an ongoing, prospective, open-label study in RRMS patients receiving intravenous 300 mg natalizumab every 4 weeks. Measures of increasing disability were assessed using as a reference either study baseline score or a "roving" system that resets the reference score after ⩾24- or ⩾48-week confirmation of a new score. Results: This analysis included 5562 patients. Approximately 70% more EDSS progression events unrelated to relapse and 50% more EDSS worsening events overall were detected with a roving reference score (cumulative probability: 17.6% and 29.7%, respectively) than with a fixed reference baseline score (cumulative probability: 10.1% and 20.3%, respectively). Conclusion: In this long-term observational RRMS dataset, a roving EDSS reference value was more efficient than a study baseline EDSS reference in detecting progression/worsening events unrelated to relapses and thus the transition to secondary progressive disease.